2020
DOI: 10.1001/jamacardio.2020.4311
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Outcomes of Preoperative Stress Testing in Total Hip and Knee Arthroplasty from 2004 to 2017

Abstract: IMPORTANCE Cardiac stress testing is often performed prior to noncardiac surgery, although trends in use of preoperative stress testing and the effect of testing on cardiovascular outcomes are currently unknown.OBJECTIVE To describe temporal trends and outcomes of preoperative cardiac stress testing from 2004 to 2017. DESIGN, SETTING, AND PARTICIPANTSCross-sectional study of patients undergoing elective total hip or total knee arthroplasty from 2004 to 2017. Trend analysis was conducted using Joinpoint and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 30 publications
0
29
0
2
Order By: Relevance
“…23 Even more recently, a 2020 study on the effectiveness of preoperative cardiac stress testing found no difference in cardiovascular outcomes between patients who did or did not have preoperative testing for their total hip replacement or total knee arthroplasty. 5 They also determined that 30,000 out of every 100,000 cardiac stress tests were unnecessary and did not decrease the frequency of adverse cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…23 Even more recently, a 2020 study on the effectiveness of preoperative cardiac stress testing found no difference in cardiovascular outcomes between patients who did or did not have preoperative testing for their total hip replacement or total knee arthroplasty. 5 They also determined that 30,000 out of every 100,000 cardiac stress tests were unnecessary and did not decrease the frequency of adverse cardiac events.…”
Section: Discussionmentioning
confidence: 99%
“…22 23 A recent cross-sectional analysis of claims data from patients who had total hip or knee arthroplasty also identified decreasing testing frequency over a similar period. 24 Our cohort study begins with a visit to a preoperative risk assessment clinic, incorporates detailed clinical data and is not limited to patients who have completed orthopaedic surgery. Our analysis, thus, extends previous understanding by showing that the reduction is not limited to orthopaedic procedures, not a result of selecting patients not referred for stress testing for elective surgery, and not consequent to lower predicted cardiac risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used administrative claims data to investigate the relationship between RCRI scores, preoperative testing, and/or MACE during the perioperative period (8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have used administrative claims data to investigate the relationship between RCRI scores, preoperative testing, and/or MACE during the perioperative period ( 8 , 9 , 10 , 11 , 12 , 13 ). Although there are limited data on patients with SLE undergoing surgery, prior studies showed that these patients had an increased risk of mortality during hospitalization after surgical procedures ( 14 , 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%